Neuromusculoskeletal disorders in the neck and upper extremities among drivers of all-terrain vehicles – a case series - Nilsson Tohr (BMC Musculoskeletal Disorders, 2004)
Abstract Background The purpose of this study was to investigate whether professional drivers of all-terrain vehicles (ATVs) with neck pain have a different array of neuromusculoskeletal disorders in the neck and upper extremities than a referent group with neck pain from the general population. It is hypothesized that exposure to shock-type vibration and unfavorable working postures in ATVs have the capacity to cause peripheral nervous lesions. Methods This study was based on a case series analyzed according to a case-case comparison design. The study population consisted of 60 male subjects, including professional drivers of forest machines (n = 15), snowmobiles (n = 15), snowgroomers (n = 15) and referents from the general population (n = 15) all of whom had reported neck pain in a questionnaire and underwent an extensive physical examination of the neck and upper extremities. Based on symptom history, symptoms and signs, and in some cases chemical, electroneurographical and radiological findings, subjects were classified as having a nociceptive or neuropathic disorder or a mix of these types. Results The occurrence of asymmetrical and focal neuropathies (peripheral nervous lesion), pure or in a mix with a nociceptive disorder was common among cases in the ATV driver groups (47%–79%). This contrasted with the referents that were less often classified as having asymmetrical and focal neuropathy (27%), but instead had more nociceptive disorders. The difference was most pronounced among drivers of snowgroomers, while drivers of forest machines were more frequently classified as having a nociceptive disorder originating in the muscles. Conclusion This study found a high prevalence of assymetrical and focal neuropathies among drivers with pain in the neck, operating various ATVs. It seems as if exposure to shock-type whole-body vibration (WBV) and appurtenant unfavorable postures in ATVs may be associated to peripheral nervous lesions.